A comparision of academic achievement of cooperative and individuali sed learning in the teaching of mathematics at senior two level at Meng o S.S. - Nsumba, Robinson (1995)
Thesis (M.Ed) - Makerere University, 1995.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (secondary) - Mengo